2019
DOI: 10.1002/chem.201904650
|View full text |Cite
|
Sign up to set email alerts
|

Do Carbon Nano‐onions Behave as Nanoscopic Faraday Cages? A Comparison of the Reactivity of C60, C240, C60@C240, Li+@C60, Li+@C240, and Li+@C60@C240

Abstract: From the analysis of the polarizability of carbon nano‐onions (CNOs), it was concluded that CNOs behave as near perfect nanoscopic Faraday cages. If CNOs behave as ideal Faraday cages, the reactivity of the C240 cage should be the same in Li+@C240 and Li+@C60@C240. In this work, the Diels–Alder reaction of cyclopentadiene to the free C240 cage and the C60@C240 CNO together with their Li+‐doped counterparts were analyzed using DFT. It was found that in all cases the preferred cycloaddition is on bond [6,6] of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…This shows another example of the non-Faraday-cage ability of fullerenes, as discussed by Solà and coworkers. [88] A similar situation is found for the ZnP 2 C 60 (2) model, where the inner region of C 60 results in an enhanced shielding of −5 ppm, owing to the contribution of the two aromatic ZnP units, which is also observed for the bent isomer (Supporting Information).…”
Section: F I G U R Esupporting
confidence: 72%
See 1 more Smart Citation
“…This shows another example of the non-Faraday-cage ability of fullerenes, as discussed by Solà and coworkers. [88] A similar situation is found for the ZnP 2 C 60 (2) model, where the inner region of C 60 results in an enhanced shielding of −5 ppm, owing to the contribution of the two aromatic ZnP units, which is also observed for the bent isomer (Supporting Information).…”
Section: F I G U R Esupporting
confidence: 72%
“…This shows another example of the non‐Faraday‐cage ability of fullerenes, as discussed by Solà and coworkers. [ 88 ]…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the solvation energy of the charged complexes are noticeably larger in comparison with [10]CPP⊃C 60 ‐MP . The difference in solvation energies for [10]CPP⊃Li + @C 60 ‐MP and other charged systems can be explained by shielding of the positive charge of Li + by the fullerene cage and its isolation from the solvent [16] . On the contrary, in [10]CPP⊃C 60 ‐MPH + and [10]CPP⊃C 60 ‐PPyMe + , the charge is localized on the pyrrolidinium moiety and, thus, accessible to the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…[15] The ground state (GS) solvation energies of CPP�Li + @C 60 -MP and other charged systems can be explained by shielding of the positive charge of Li + by the fullerene cage and its isolation from the solvent. [16] On the contrary, in S3, Supporting Information. Usually, the dipole moments of CT states are significantly larger than those of LE states.…”
Section: Solvent Effectsmentioning
confidence: 99%
“…In principle each AB pair should experience three separate electrostatic interactions, which are: (i) the charged core of A interacting with the charged core of B; (ii) an interaction between the charged cores and the charged cages; and (iii) an interaction between the charged cage of A and the charged cage of B. However, a range of experimental and theoretical studies have shown that fullerene molecules act as Faraday cages, 51–58 which means that entities (other cores and cages) external to a given cage are shielded from any charge contained within the cage, i.e. the metal or halogen core.…”
Section: Case Studies and Discussionmentioning
confidence: 99%